2019
DOI: 10.1007/s10661-019-7876-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of air purifier on efficient removal of airborne bacteria, Staphylococcus epidermidis, using single-chamber method

Abstract: We evaluated the efficiency of an air purifier using the single-chamber method for the effective removal of airborne Staphylococcus epidermidis, a nosocomial infection-causing bacterium. In this experiment, the bacterial strain S. epidermidis was injected using a nebulizer into the test chamber, which was similar to a consumer living space (60 m 3 ). The microbial sampling was conducted via the air sampler method, and the reduction in S. epidermidis growth was monitored by performing three consecutive tests. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…They are also important pathogens, especially in hospitals, because it is more common for them to infect immunocompromised patients. The main route of transmission for Staphylococcus bacteria is the contact route, but indoor air testing indicates the presence and the possibility of long-term survival of numerous bacteria of this genus in the air (Becker et al 2014 ; Lee et al 2019 ; Lenart-Boroń et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…They are also important pathogens, especially in hospitals, because it is more common for them to infect immunocompromised patients. The main route of transmission for Staphylococcus bacteria is the contact route, but indoor air testing indicates the presence and the possibility of long-term survival of numerous bacteria of this genus in the air (Becker et al 2014 ; Lee et al 2019 ; Lenart-Boroń et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The achieved levels of reduction are similar to other, non-commercial devices. Huang et al [36] reached 75-85% reduction in bacterial aerosol and 80-90% reduction in fungi, while Lee et al [37] reported 79-82% reduction in bioaerosols. The reported levels are higher than in our more effective construction without a carbon filter; however, both reported devices used HEPA filters, which increase the cost of such an air purifier.…”
Section: Effectiveness Of Bioaerosol Removal By a Low-cost Air Purifiermentioning
confidence: 99%
“…Endotoxin 29%-37% [17] Not commercial device HEPA filter device and UV filter Bioaerosols 79%-82% [37] Aerobiotix Illuvia 500uv system (Aerobiotix, West Carrollton, OH, USA)…”
Section: Ionic Air Purifiersmentioning
confidence: 99%
“…However, it has not been tested for bacterial species, and the purification effect of each microorganism cannot be seen directly. Some researchers used aerosol generators to artificially make certain types of microorganisms into aerosols, and verified the purifying effect of air purifiers in the ideal environment of a closed experimental chamber (Lee et al, 2019). Although all the above can intuitively reflect the purification effect, it is not an evaluation of the purification effect of the microorganisms that actually exist in the environment under the dynamic environment of the hospital's normal diagnosis and treatment.…”
Section: Accepted Manuscriptmentioning
confidence: 99%